(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with individual uniqueness of writer in the selection of the verbal means of the world scene’s recreation; with the peculiarities of realization of the belletristic style’s opportunities according to the esthetic author’s intrntion.